2007
DOI: 10.1159/000107098
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Differences in Human Brain Activity Using a Face- and Location-Matching Task: An fMRI Study

Abstract: Purpose: To evaluate the differences of cortical activation patterns in young and elderly healthy subjects for object and spatial visual processing using a face- and location-matching task. Materials and Methods: We performed a face- and a location-matching task in 15 young (mean age: 28 ± 9 years) and 19 elderly (mean age: 71 ± 6 years) subjects. Each experiment consisted of 7 blocks alternating between activation and control condition. For face matching, the subjects had to indicate whether two displayed fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Advanced neuroimaging techniques provide promising avenues to verify the neural correlates of the declined face processing in old adults. Evidence from studies using task‐fMRI techniques have shown that the cognitive declines of face processing may be related to reduced neural selectivity (Koen & Rugg, 2019; Leinsinger et al, 2007; Reuter‐Lorenz & Park, 2010). Specifically, it is characterized by the reduced neural response to faces relative to other control stimuli in the fusiform face area (FFA) and the occipital face area (OFA; Goh et al, 2010; Lee et al, 2011; D. C. Park et al, 2004; J.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advanced neuroimaging techniques provide promising avenues to verify the neural correlates of the declined face processing in old adults. Evidence from studies using task‐fMRI techniques have shown that the cognitive declines of face processing may be related to reduced neural selectivity (Koen & Rugg, 2019; Leinsinger et al, 2007; Reuter‐Lorenz & Park, 2010). Specifically, it is characterized by the reduced neural response to faces relative to other control stimuli in the fusiform face area (FFA) and the occipital face area (OFA; Goh et al, 2010; Lee et al, 2011; D. C. Park et al, 2004; J.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from studies using task-fMRI techniques have shown that the cognitive declines of face processing may be related to reduced neural selectivity Tianying Qing and Jing Chen contributed equally to this article. (Koen & Rugg, 2019;Leinsinger et al, 2007;Reuter-Lorenz & Park, 2010). Specifically, it is characterized by the reduced neural response to faces relative to other control stimuli in the fusiform face area (FFA) and the occipital face area (OFA; Goh et al, 2010;Lee et al, 2011;D.…”
Section: Introductionmentioning
confidence: 99%
“…The main brain areas showing activation in response to such visuospatial tasks include the medial (including paracentral lobule and precuneus) [3,22,23] and dorsal parietal cortex (BA 7) [24] ; temporoparieto-occipital cortex [10,[25][26][27][28] ; frontal regions, including medial frontal, cingulate [22,28] and medial and lateral premotor cortices [29] . Few neuroimaging trials have examined the effects of AChEI treatment.…”
mentioning
confidence: 99%
“…Cropping the image to an oval shape that reveals only these features ensures that face recognition concentrates on these essential facial features. Moreover, a more or less oval mask has proven to be appropriate in previous research (e.g., Bokde et al, 2005;Leinsinger et al, 2007;White & Li, 2006).…”
mentioning
confidence: 99%